Performance analysis and optimization of cooperative spectrum sensing for maximizing secondary throughput - LI Mei-ling1; YUAN Chao-wei1; LI Lin1; YANG Rui-zhe3 (Tongxin xuebao)
The relationship among SU,detection threshold,bandwidth,spectrum utilization and secondary throughput in cognitive radio networks was analyzed,which indicates the lower false alarm probability,higher spectrum utilization and larger secondary throughput with less SU in C-CSS（censoring based cooperative spectrum sensing）,besides,the required detection threshold for maximizing the secondary throughput different with the traditional CSS under given SU number and the objective demand.Based on the NP criticism,an optimal cooperative spectrum sensing algorithm for maximizing the secondary throughput was proposed by solving the mathematic model to obtain the optimal party of SU and detection threshold.Theoretical analysis and simulation results show that the maximized secondary throughput achieved by the proposed optimal algorithm,while maintaining the given detection probability.